TERJEMAHAN CERITA ANAK USHIKATA TO YAMANBA KARYA TSUBOTA JÅJI - , RETNO WULANDARI; , Wiastiningsih, S.S, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final assignment is a translation of children literature work entitled Ushikata to Yamanba by Tsubota JÅji. This story tells about an oxdriver who has to escape from Yamanba, a female demon who has magical power. The author is interested in choosing the translation as the topic of the assignment because the author wants to apply the materials which have been studied throughout the course. Therefore, the author translates a children literature work from Japanese to Indonesian. In the translation process, the author uses word by word translation method and communicative method. Word by word method is used at the first translation process to understand the grammar and interpret the difficult text. Communicative method is used because this method is applied to maintain the equivalent contextual meaning from the source language,therefore, the readers are able to understand the message in the target language. Difficulty in the translation process experienced by the author is there are many words written in hiragana. Hence the author has a problem in finding the meaning. The author solves the problem by using kanji dictionary application. The other difficulty is adjusting the wordâs equivalent from Japanese to Indonesian. The author looks in for many references such as translated story, Kamus Besar Bahasa Indonesia and applies suggestion from the supervisor to solve the problem. This story, Ushikata to Yamanba by TsubotaJÅji, has a moral value which tells the readers whenever we face a trouble and get an opportunity, we must use it wisely and do not waste it.